BEST PROXIMITY THEOREMS FOR REICH TYPE CYCLIC ORBITAL AND REICH TYPE MEIR-KEELER CONTRACTION MAPS - Karapinar, E.; Sankara raju kosuru, G.; Tas, K. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
In this manuscript, Reich type cyclic orbital contraction and Reich typeMeir Keeler cyclic contraction are defined and also some related best proximity point theorems are obtained. These theorems generalize some results of Kirk-Srinavasan-Veeramani and Karpagam-Agrawal.